Virtual onboarding: Using the metaverse for induction of new employees on remote work - Carlos Fernandes; Dias, J.; Costa, P. (ICGI 2024 - 6th International Conference on Graphics and Interaction, Proceedings, 2024)
This paper explores the integration of metaverse and Virtual Reality (VR) technologies into remote employee onboarding processes within a multinational company. The study compares traditional remote onboarding methods with a newly developed metaverse-based solution. The evaluation focuses on employee engagement and knowledge retention during the onboarding process. Key results indicate that the metaverse-based approach enhances engagement and retention, offering practical insights for companies seeking to adopt VR solutions for onboarding.